2014
DOI: 10.1111/jep.12140
|View full text |Cite
|
Sign up to set email alerts
|

Rasch analysis of the illness management and recovery scale‐clinician version

Abstract: Rationale, aims and objectives The illness management and recovery scale-clinician version (IMRS-C) is a measure of outcomes thought to be important indicators of progress for consumers participating in illness management and recovery (IMR). Prior research has examined the psychometric properties of the IMRS-C; extant research supports certain aspects of the scale's reliability (test-retest) and validity (sensitivity to interventions). Analyses based on Rasch provide certain advantages and have not been applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Another critical element of IMR is cognitive behavioral therapy (CBT) techniques (McGuire et al, 2014). Numerous clinical trials and some meta-analysis have shown that CBT is an effective and cost-efficient treatment for symptom reduction and management in people with a range of severe mental illnesses (van der Gaag, 2014), including schizophrenia (Wykes, Steel, Everitt, & Tarrier, 2008), major depressive disorders (Cuijpers et al, 2013), and bipolar disorder (Szentagotai & David, 2010).…”
Section: Critical Elements Of Imrmentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical element of IMR is cognitive behavioral therapy (CBT) techniques (McGuire et al, 2014). Numerous clinical trials and some meta-analysis have shown that CBT is an effective and cost-efficient treatment for symptom reduction and management in people with a range of severe mental illnesses (van der Gaag, 2014), including schizophrenia (Wykes, Steel, Everitt, & Tarrier, 2008), major depressive disorders (Cuijpers et al, 2013), and bipolar disorder (Szentagotai & David, 2010).…”
Section: Critical Elements Of Imrmentioning
confidence: 99%
“…These elements were used as the foundation for IMR (Gingerich & Mueser, 2004). In a subsequent effort, McGuire and colleagues (2014) utilized an expert survey to establish agreement regarding a total of sixteen critical elements of IMR. Each of these elements has been independently linked with consumer outcomes.…”
mentioning
confidence: 99%
“…The IMRS was selected as a widely used measure of recovery tailored specifically to the treatment targets of the IMR program (McGuire, Kean, Bonfils, Presnell, & Salyers, 2014; Scheyett, DeLuca, & Morgan, 2013). Illness self-management is a key outcome of the IMR intervention and accordingly, was used to assess level of treatment response.…”
Section: Methodsmentioning
confidence: 99%
“…Despite robust evidence for overall treatment effects, consumers receiving IMR vary substantially in their responsiveness (McGuire et al, 2014). Moreover, in our recently completed multi-site trial (see Methods section for description), only 38% of consumers with SMI demonstrated a substantial increase in illness self-management (McGuire et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation